2014
DOI: 10.1007/s00268-014-2621-0
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Current Management and Treatment Options for Superficial Venous Insufficiency

Abstract: The recognition of lower extremity venous disease as a significant cause of morbidity and lower quality of life, afflicting up to 25 % of Western populations, has led to rapid and drastic improvements in treatment options as well as an increasing awareness of the disease. Superficial venous disease, a frequent medical problem encountered in clinical practices, is now a common reason for referral to providers offering a spectrum of interventions. Venous guidelines have been set forth by the American Venous Foru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 68 publications
(83 reference statements)
0
3
0
1
Order By: Relevance
“…Using a higher-pressure compression stocking could have led to arterial complications. In addition, the act of leg elevation while sleeping was an additional aid alleviate the venous insufficiency [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using a higher-pressure compression stocking could have led to arterial complications. In addition, the act of leg elevation while sleeping was an additional aid alleviate the venous insufficiency [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phlebectomy (also known as microphlebectomy or stab avulsion) is used to target bulging varicose veins closer to the surface of the skin. This technique is highly recommended for tortuous distal varicosities and offers improved cosmetic results and decreased risk of blood clots [ 157 ]. Phlebectomy may be performed via a conventional multiple stab technique; recently, however, transilluminated powered phlebectomy (TIPP), in which transillumination is used to guide mechanical vein avulsion following hydrodissection using tumescent anesthesia, has gained popularity due to its minimally invasive nature and ease of use.…”
Section: Advances In Surgical Managementmentioning
confidence: 99%
“…However, large varicose veins require additional procedures such as ambulatory phlebectomy or stab avulsion. 6 Direct varicose ablation is not common in general practice. A study by Park et al, published in 2007, suggested that direct laser ablation couldn't replace classic methods for treating branch varicosities because of the high failure rate and risk of burned skin.…”
Section: Introductionmentioning
confidence: 99%